The Effectiveness of Reflexology Massage to The Reduction of Blood Sugar Level of Elderly with Type 2 Diabetes Mellitus - Levi Tina Sari; Wahyu Wibisono; Nevy Norma Renityas (STIKes Patria Husada Blitar, 2022)
Chronic hyperglycemia in clients with diabetes mellitus will cause long-term damage, namely dysfunction or failure of organs such as eyes, kidneys, nerves, heart and blood vessels. Therefore, reflexology on the soles of the feet is become one of the complementary therapies that has no side effects. The research design used pre-experimental approach with a one group pretest-posttest design. The data analysis was divided into two, namely univariate analysis by frequency distribution and bivariate analysis by paired sample t-test. The results showed that there was a difference in the points of before and after treatment as much as 36.15 points. There was an effect between reflexology treatment before and after as much as 0.0001 < 0.05. Reflexology could respond the hypothalamus, activated the Hypothalamus-Pituitary-Adrenal AXIS, and produced corticotropin releasing factor (CRF) hormone which stimulated the pancreas to increase insulin synthesis. One of the receptors on target cells, namely the glucose transporter (GLUT 4) which functioned to bring glucose into cells and accelerated the use of glucose which resulted in lower blood glucose levels. Reflexology can be done by oneself and has no side effects.